Sustainable Digital Accounting: Integrating ESG Reporting and Data Analytics in the Era of Industry 5.0 - Rusli Nugraha; Avradya Mayagita; Arief Satriansyah; Rina Oktiyani (Jurnal Visi Manajemen, 2026)
This study explores the conceptual integration of Environmental, Social, and Governance (ESG) reporting and data analytics within the framework of sustainable digital accounting, with Industry 5.0 acting as a moderating paradigm. As organizations increasingly face demands for transparency, ethical governance, and sustainable operations, the limitations of traditional accounting systems have become evident. ESG reporting plays a crucial role in communicating non-financial performance and guiding strategic decisions aligned with stakeholder interests and regulatory expectations. However, the effectiveness of ESG disclosures is often hindered by fragmented data structures, inconsistent standards, and insufficient technological support. Data analytics, when integrated into ESG processes, enhances the precision, timeliness, and reliability of sustainability disclosures through predictive modeling, anomaly detection, and real time performance monitoring. Yet, despite its potential, the adoption of data analytics in accounting remains limited and under-theorized. Industry 5.0 introduces a human centric approach to technological transformation, emphasizing ethical innovation, inclusivity, and resilience. By positioning Industry 5.0 as a contextual and moderating framework, this study offers a novel perspective on how ESG and data analytics can synergize to create ethically aligned, future-ready accounting systems. Employing a systematic literature review, the research develops a conceptual model linking ESG, data analytics, and Industry 5.0, providing insights for academics, practitioners, and policymakers aiming to embed sustainability into digital accounting systems. The findings underscore the importance of aligning digital tools with ethical and societal values to advance accountable and sustainable business practices..